Building the microbiota in strawberry soilless cultivation systems with on-farm AMF inoculants: Roles in yield, phytochemical profile, and root morphology - Chiomento, José Luís Trevizan; De Nardi, Fabiola Stockmans; Fante, Rudinei; Dal Pizzol, Emanuele; dos Santos Trentin, Thomas; Borba, Aline Chitolina; Basílio, Letícia Silva Pereira [UNESP]; dos Santos Garcia, Vitor Augusto [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (Elsevier, 2025)
Arbuscular mycorrhizal fungi (AMF) can be a biostrategy for building up the microbiota of the substrate used to grow strawberries. The aim of the study was to investigate whether the use of on-farm AMF inoculants interferes with the horticultural potential of strawberry, ‘Monterey’ cultivar, in the soilless cultivation system. The treatments tested were the absence (control) and the presence of four on-farm AMF inoculants (Acaulospora morrowiae, Glomus intraradices, Rhizophagus clarus, and mycorrhizal community), in a randomized block design, with four replications. R. clarus and AMF community were more efficient in increasing the monthly fruit yield. Fruits with the best ratio between sugar content and acidity were produced by plants treated with AMF community. Mycorrhized plants produced fruit with the highest total flavonoid and polyphenol contents. The highest amount of phytochemicals detected in ‘Monterey’ leaves was observed in plants cultivated with AMF community. All the plants cultivated with AMF developed a more robust root system, with A. morrowiae and G. intraradices standing out. We conclude that the monospecific and multispecific inoculants used help to build up the microbiota of the growing substrate. This is reflected in the better root volume and in the biosynthesis of secondary metabolites in the plants.